Relation between household food insecurity and breastfeeding in Canada - Orr, Sarah K. (CMAJ, 2018)
BACKGROUND: Qualitative studies have suggested that food insecurity adversely affects infant feeding practices. We aimed to determine how household food insecurity relates to breastfeeding initiation, duration of exclusive breastfeeding and vitamin D supplementation of breastfed infants in Canada. METHODS: We studied 10 450 women who had completed the Maternal Experiences — Breastfeeding Module and the Household Food Security Survey Module of the Canadian Community Health Survey (2005–2014) and who had given birth in the year of or year before their interview. We used multivariable Cox proportional hazards models and logistic regression to examine the relation between food insecurity and infant feeding practices, adjusting for sociodemographic characteristics, maternal mood disorders and diabetes mellitus. RESULTS: Overall, 17% of the women reported household food insecurity, of whom 8.6% had moderate food insecurity and 2.9% had severe food insecurity (weighted percentages). After adjustment for sociodemographic factors, women with food insecurity were no less likely than others to initiate breastfeeding or provide vitamin D supplementation to their infants. Half of the women with food insecurity ceased exclusive breastfeeding by 2 months, whereas most of those with food security persisted with breastfeeding for 4 months or more. Relative to women with food security, those with marginal, moderate and severe food insecurity had significantly lower odds of exclusive breastfeeding to 4 months, but only women with moderate food insecurity had lower odds of exclusive breastfeeding to 6 months, independent of sociodemographic characteristics (odds ratio 0.60, 95% confidence interval 0.39–0.92). Adjustment for maternal mood disorder or diabetes slightly attenuated these relationships. INTERPRETATION: Mothers caring for infants in food-insecure households attempted to follow infant feeding recommendations, but were less able than women with food security to sustain exclusive breastfeeding. Our findings highlight the need for more effective interventions to support food-insecure families with newborns.